(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This is an effort to measure the trends and growth in the receipts i.e., revenue as well as capital receipts of the Government of India. For this purpose data have been collected for five years primarily from the websites of ministry of finance, Government of India from 2013-14 to 2017-18. The assembled data have been analyzed with the help of various statistical tools techniques such as trend analysis, mean score, standard deviation and CAGR. The study brought out increasing trends in both types of receipts- revenue receipts and capital receipts. Revenue receipts found to be more increasing (CAGR=7.18 ) in comparison to capital receipts (CAGR=5.35 ). There was registered a more fluctuation in revenue receipts in comparison to capital receipts during the period of study.